Asymmetrical Functional Deficits of ON and OFF Retinal Processing in the mdx3Cv Mouse Model of Duchenne Muscular Dystrophy - Tsai, Tina I.; Salgueiro Barboni, Mirella Telles; Nagy, Balazs Vince; Roux, Michel J.; Rendon, Alvaro; Ventura, Dora Fix; Kremers, Jan (Investigative Ophthalmology & Visual Science, 2016)
The dystrophin mouse mutant mdx3Cv exhibits scotopic electroretinograpic (ERG) abnormalities, which resemble clinical changes observed in Duchenne muscular dystrophy (DMD) patients. In the present study, ERGs obtained from mdx3Cv and their wild-type littermates under scotopic, mesopic, and photopic conditions were analyzed to provide further insight on the affected retinal pathways, and to compare them with human data.Electroretinograms of mdx3Cv (n = 9) and age-matched C57BL/6J mice (n = 10) included the scotopic full-field flash (for outer retinal deficits in rod pathway), scotopic threshold response (for inner retinal integrity), photopic flash, sinusoidal flicker (for outer retinal deficits in cone pathway), mesopic rapid-on/-off sawtooth flicker, and photopic long-duration flash measurements (for separate ON-/OFF-responses under different conditions).The mdx3Cv mice exhibited diminished and delayed scotopic and photopic ERGs, particularly in their b-wave and oscillatory potentials. Interestingly, homologues to the a- and b-wave of the mesopic ON-response were affected in their peak/trough times but not in their amplitude, whereas changes to both features were uncovered for photopic ON-response and sinusoidal flicker. Mesopic and photopic OFF-components were within the norm.Abnormal scotopic and photopic flash ERGs were observed in mdx3Cv, which corroborate with deficits that are likely restricted to the level of photoreceptor-to-bipolar cell transmission. Further overlaps between mdx3Cv mice and DMD patients exist, including asymmetrical ON versus OFF ERG alterations under mesopic versus photopic vision. In mice, ON-pathway function is compromised, whereas the OFF-pathway is spared.
EVALuna2:21316
Keywords: Duchenne muscular dystrophy; dystrophin; electrophysiology; mouse model